Homo- and Dikaryons of the Arbuscular Mycorrhizal Fungus Rhizophagus irregularis Differ in Life History Strategy - Serghi, Edward Umberto; Kokkoris, Vasilis; Cornell, Calvin; Dettman, Jeremy; Stefani, Franck; Corradi, Nicolas (Frontiers in Plant Science, 2021)
Arbuscular mycorrhizal fungi (AMF) are obligate plant symbionts that have the potential to improve crop yield. These multinucleate organisms are either homokaryotic (AMF homokaryons) or heterokaryotic (AMF dikaryons). In AMF dikaryons thousands of nuclei originating from two parental strains co-exist in the cytoplasm. In other fungi, homokaryotic and dikaryotic strains show distinct life history traits (LHT) such as variation in growth speed and fitness, but how such traits compare between AMF dikaryons and homokaryotic relatives is unknown. To address this, we measured 20 life history traits across three root organ cultures (Carrot, Chicory, Nicotiana) for 10 phylogenetically distinct strains (four dikaryons, six homokaryons) of the model species R. irregularis. Our analyses show that AMF dikaryons have clearly distinct life history strategies (LHS) compared to AMF homokaryons. In particular, while AMF homokaryons have significantly higher germination ability and germinate faster, AMF dikaryons grow significantly faster and create a more complex hyphal network post-germination across hosts. These findings link nuclear organization with the emergence of key ecological and evolutionary traits in a widespread group of multinucleate plant symbionts.